Daca x×(y-z)=2.4 si x×(z+t)=3.1,calculati x×2.4×(y+t)=?
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
13.2
Explicație pas cu pas:
x(y - z) = 2.4
x(z + t) = 3.1
adunam relatiile
xy - xz + xz + xt = 2.4 + 3.1
xy + xt = 5.5
x(y + t) = 5.5
x·2.4·(y + t) =
= 2.4·x·(y + t)
= 2.4·5.5
= 13.2
Răspuns de
1
Răspuns:
x(y-z)=2,4
x(z+t)=3,1
xy-xz+xz+xt=2,4+3,1
xy+xt=5,5
x(y+t)=5,5
x·2,4·(y+t)=2.4·x·(y+t)=2,4·5,5=13,2
Alte întrebări interesante
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Informatică,
9 ani în urmă